Awareness Video Creations to Support Rookvrije Voetbalstadions in FC Twente - Fenny Pangestu; Tim Roosen; Henri Bruel (Jurnal Desain Komunikasi Visual Nirmana, 2020)
A "no smoking" policy as part of Rookvrije Voetbalstadions or Smoke-free Football Stadiums Campaign will be applied in all soccer stadiums below the Eredivisie and Keuken Kampioen Divisie starting the season 2020/2021. As one of those soccer stadiums, FC Twente has several problems realizing the "no smoking" policy. First is the online issue; lack of media as a source of information and knowledge. Second is the offline issues; no "no smoking" sign inside the stadium and minimum enforcer source. These problems lead to the reason for the unawareness situation of their smoking visitors. An Awareness Video has been made to help FC Twente raise their smoking visitors' awareness of the "no smoking" policy inside the stadium. The writer has done observation on the stadium, researched FC Twente's fans, and analyzed both, using Design Thinking Methodology as the framework.